Formation and Fulfillment of ’Homing Desire’ in Ghimire’s "Diaspora" - Timalsina, Ramji (JODEM: Journal of Language and Literature, 2019)
Where is the home of Nepali diasporans? Is Nepal still their home? The recent theory of diaspora questions the traditional notions of home and homeland. Their place has been taken by the discourse of ‘homing desire’ that is the desire to make a home in the host land. Such a home has the quality of both of the homes that is the home they have left behind and the standard home they see in the host land. In Nepali Diaspora, too, such a theme has crept into literary creations. In this article Hari Ghimire’s poem “Diaspora” has been analysed so as to see how it depicts the development of ‘homing desire’ and its fulfilment. The speaker of the poem, in the beginning, expresses his desire to home, i.e. feel comfortable, himself in the diaspora. Later he is happy because of the fulfilment of the desire. This analysis is primarily based on Avtar Brah’s theory of ‘homing desire’. The insights of Salman Rushdie’s idea of ‘imaginary homeland’ and Sara Ahmed’s concept of home in the globalized time have been used to support and extend Brah’s theoretical stand. It is hoped that this article will encourage further discourse on ‘homing desire’ in the study of Nepali Diaspora and its literature.